IP (Intellectual Property) CAD Validation Solution using Crossfire - Aneja, Anshul (My University, 2017)
Developments in the innovation business has made our every day life simpler than at any other time. Gadgets like cell phones, touch sensors, desktops and numerous different parts of advanced world are being more proficient and more astute every day. Each one of these gadgets contains silicon chip which is intended to perform a specific task. Intellectual Property (i.e. IP) inside a silicon chip is a portable design that can be re-utilized. An IP is a block of basic functionality that is licensed to various vendors/organizations when utilized in different silicon chip designs. An Intellectual Property contains various views like CDL (Circuit Design Language), GDS (Graphical Design System), LEF (Library Exchange Format), etc. So as to make a gadget's working right, one needs to approve IP which thusly prompts towards validation of IP CAD Views or the Library Views. Validation is an exceptionally pivotal part in the evolution of an IP. IP Validation is possible done using two different methodologies i.e. either through Manual Validation or through Automated Validation. Manual IP CAD Validation is executed by an individual with no assistance of any tool/software. However, due to some confinements like less precise outcome, less reliability and time consuming process, we prefer automated IP validation which is executed with the assistance of a tool/software. IP CAD validation is a vital process that helps the user or designer to detect critical defects prior to be use inside a real SoC design. This calls for the need of an IP CAD validation solution that precisely confirms the accuracy and adequacy of the IP design. This is where the IP Validator (IPV) comes into the picture. IPV is a Unified Framework that encapsulates all checks for an efficient and optimized IP Validation. It also includes Crossfire tool (from Fractal Technologies) as one of its component. In this thesis, a versatile IP CAD Validation Solution has been proposed that provides an escalated validation of different CAD views while hiding all the complexities from the user and in this way expanding the convenience.
M.E. thesis
Keywords: IP; Crossfire; CAD validation